Stability and Marginal Bone Loss with Three Types of Early Loaded Implants During the First Year After Loading - (:unkn) unknown (QUINTESSENCE PUBLISHING CO INC, 2012)
Purpose: To determine the change in stability of three different implant systems using resonance frequency analysis (RFA) and to correlate RFA measurements with factors related to implant design, length, and diameter, patient gender, and dental arch. Clinical and radiologic evaluations were performed up to 1 year after loading. Materials and Methods: Three different types of implants from three different manufacturers were inserted in the posterior maxilla and mandible. RFA measurements were performed at implant placement and weekly up to 8 weeks postoperatively and were compared with respect to implant type, length, and diameter and dental arch. The implants were loaded after 8 weeks. All implants were examined radiographically at baseline and at 6 and 12 months. Plaque Index, Sulcus Bleeding Index, peri-implant probing depths, and marginal bone loss were recorded. Repeated-measurements analysis of variance, two-tailed mixed-model analysis of variance, the Least Significant Differences and Mann-Whitney U tests were used for statistical analyses. Results: All the groups showed high stability values at all time points (above 71). There were statistically significant differences between groups at all time points except 1 and 2 weeks. Mandibular implants showed statistically higher stability values than maxillary implants. Wide implants showed statistically higher stability values than narrow implants. Mean marginal bone loss was 0.22 +/- 0.47 mm after 1 year. Conclusions: All three implant systems showed clinically acceptable stability values prior to early loading. The success rates and bone loss were similar to the values reported in the literature. INT J ORAL MAXILLOFAC IMPLANTS 2012;27:162-172
Keywords: early loading; implants; implant stability; resonance frequency analysis; RESONANCE FREQUENCY-ANALYSIS; ENDOSSEOUS DENTAL IMPLANTS; CONTROLLED CLINICAL-TRIAL; SINGLE-TOOTH IMPLANTS; FOLLOW-UP; POSTERIOR MAXILLA; SLA IMPLANTS; EDENTULOUS MAXILLA; TITANIUM IMPLANTS; ETCHED IMPLANTS